Retrofitting of an Existing Box Type Culvert using NDT and Analysis Tool Staad.Pro - Singh, Singasan; Diwan, P. C. (International Journal of Scientific Research in Civil Engineering, 2019)
As India is a developing nation which requires a good flow of transportation by means of road, air, rail and water for its proper and easy connectivity. For study we determine its present strength using N.D.T. test (rebound hammer) than we use analysis tool staad.pro to determine the best way of strengthening the structure by retrofitting technique using its existing strength and determine the variation in strength after retrofitting. Here I concluded that with the help of retrofitting technique we can provide strength and justify that staad.pro helped in implementing strengthening technique with present discharge rate and loadings without affecting the structure.